MODERN APPROACHES TO ESTIMATE THE QUALITY OF EDUCATION IN THE WORLD AND RUSSIAN ECONOMY - A. Tisyachin; O. Mihaylov (Вестник университета)
In this article the study of international experience on ensuring quality of educational services at the present stage. Major global trends and approaches leading educational organizations based on the development of internal self-monitoring system of the total quality management and a «quality culture». Based on the study the author formulates proposals for the improvement and further development of the concept of total quality management, an assessment of the educational system of Russia at the present stage.